IDENTIFIKASI ISOLAT MONASCUS SP. HASIL ISOLASI ANGKAK BERDASARKAN GEN INTERNAL TRANSCRIBED SPACER (ITS) DAN PENGUKURAN KANDUNGAN PIGMEN - Mia Tri Wardani; Endang Kusdiyantini; Anto Budiharjo (Jurnal Akademika Biologi, 2017)
The Identification of Monascus based on their morphological characteristic, this methods is very problematic due to several  specimens share similarity on morphology and colours. Nowadays, the identification of molecular based organisms has been done to complement morphological identification, for example mold identification using the Internal Transcribed Spacer (ITS) gene. The objectives of study were to identify of Monascus isolates the result of angkak isolation using Internal Transcribed Spacer (ITS) gene, phylogenetic analyzing,  determination cell growth and determination of production pigment content. Sequences of  ITS Monascus were amplified using PCR and the molecular phylogenetic  analyses was using Neighbor Joining (NJ) method. Based on homology search by Basic Local Alignment Search Tool (BLAST) program and phylogenetic tree analyses, mold of isolates were identified as the Monascus purpureus (100%). The amplified DNA fragments were about 553 bp. Determination of Monascus mold cell growth were carried out by the method of dry weight cell. Determination of pigment by using spectrophotometer at 390 nm wavelength for yellow pigment and 500 nm for red pigment. The result of determination of Monascus mold pigment content show that have increased during fermentation time until day 13. The amount of yellow extracellular pigment production is 37.358 U / g; While the red color pigment of 2.6545 U / g. The amount of red intracellular pigment production is 7.4175 U / g, while the yellow pigment is 30.176 U / g.Keywords: Monascus, angkak, molecular phylogenetic, pigment